Sequential assignment of the intrinsically disordered protein bacterial interleukin receptor 1 with nuclear magnetic resonance spectroscopy - Salovaara, Santeri (2018)
Significance of intrinsic disorder in biological systems, nuclear magnetism and different methods for its use in protein structure determination have been reviewed. These methods include the use of different detection schemes for nuclear magnetic resonance spectroscopy, observables and their relation to structure, computational methods and sequential assignment procedure. In addition an intrinsically disordered protein, bacterial interleukin receptor 1, related to pathological pathways of periodontitis is covered in in detail. Sequential backbone chemical shift assignment and structural propensity estimation calculations based on chemical shifts of bacterial interleukin receptor 1 have been carried out. Secondary structure estimation confirms that bacterial interleukin receptor 1 is an intrinsically disordered protein with some transient alpha-helicity in the middle of its primary structure.